Penanganan Gizi Buruk kepada Ibu Hamil - Devi Handayani; Eva Fauzia; Aisyah Nurjanah (Jurnal Forum Kesehatan : Media Publikasi Kesehatan Ilmiah, 2021)
Abstract – The development of the fetus can be impacted by the mother's nutritional state both before and during pregnancy. fetus in the process of conception. if the mother's dietary intake is consistent before and during pregnancy, it is expected that she will have a healthy kid in a few months who will be of average weight. In other words, the mother's nutritional status affects the quality of the baby that is born. During and before pregnancy. In Indonesia, there are still many pregnant women who are undernourished. This is what prompts a research for the government to solve this as it continues to rise year after year. problem. The government is still working to lower neonatal and under-five death rates by keeping an eye on and keeping track of the decline in the nutrition's widespread use. Numerous initiatives are taken to enhance community nutrition, such as stepping up the exclusive breastfeeding program (ASI), combating micronutrient deficiencies, and providing pregnant women with iron supplements, vitamin A, taburia, salt that has been iodized, and management of malnutrition and malnourished patients. becomes essential for government initiatives.